Achievement goal orientation and stimulant misuse in college students. Issue 2 (17th February 2021) - Antshel, Kevin M.; Parascandola, Theresa; Taylor, Lea E.; Faraone, Stephen V.
Abstract: Objective: The prevalence of stimulant medication misuse is rising in college students. Motivations to use stimulant medications differ from motivation to use other substances such as alcohol or cannabis. However, no previous research has examined the impact of achievement goal orientation on stimulant misuse in college students. Participants: 309 college students (mean age = 18.9; 117 males) without an ADHD diagnosis were invited to participate. Methods: Participants completed an online research questionnaire that assessed factors associated with stimulant medication misuse as well as achievement goal orientations (Learning and Performance Orientations). Results: Approximately 12% endorsed a history of stimulant misuse within the past year. More males (17.1%) than females (9.4%) reported stimulant misuse. Those with and without a history of stimulant misuse differed on Performance Orientation (misuse > no misuse) yet were comparable on Learning Orientation. Conclusions: Having a higher Performance Orientation independently predicted stimulant misuse.